On Finite Groups with Permutable Generalized Subnormal Subgroups - Velesnitskii, V. F.; Semenchuk, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the Kegel–Shemetkov problem of finding the classes of finite groups \( {\mathfrak F} \) such that, in any finite group, the product of permutable \( {\mathfrak F} \) -subnormal subgroups is a \( {\mathfrak F} \) -subnormal subgroup.